Numerical Analysis of Stress and Temperature Fields in a Composite Stratum Based on a New Method of Shield Construction for Safety and Environmental Protection - Wei Dai (International Journal of Environmental Research and Public Health, 2020)
Safety and environmental protection are key issues in shield construction. Due to wear, the cutter of a shield machine must be changed after a period of excavation. In order to realize the tool change operation of a shield machine at atmospheric pressure, a method of cutter head freezing of the shield machine is described in this paper. The finite element simulation method is used to analyze the construction of a shield machine with a frozen cutter head in a composite stratum. For a composite stratum with uneven hard and soft layers in a ratio of 1:1, the stress and temperature fields are analyzed, and the stress change around the hob is recorded. Through numerical simulation, the change of the temperature field around the shield machine is determined in real time. As time goes on, the temperature around the shield machine decreases, and the frozen range expands. When the temperature field in a specific point reaches a critical value, the temperature at that point will remain constant, and the stress field around the cutter head will also tend to become stable. The isothermal region of the soil presents an annular distribution, and the final temperature tends to be stable and gradually increase as the distance from the frozen cutter head increases. The final temperature of the monitoring area reaches a stable value corresponding to −26.5 °C, the axial depth of the frozen wall is more than 2.5 m, the minimum frozen radius is 3.2 m, the stress distribution around the cutter head is unbalanced, the maximum stress is measured in the hard rock layer, and the stress around the cutter head at the hob level indicates that tool change is necessary. Compared with the traditional method, the construction method of a frozen cutter head is more effective and more environmentally friendly. Further research will allow a broad application of this method in shield excavation in a composite stratum.